Intestinal Parasitosis - Shakya, Bikash; Bhargava, D; Shrestha, S.; Rijal, B. P. (Journal of Institute of Medicine Nepal, 2010)
Introduction: Intestinal parasitosis is highly prevalent among general population and hospital patients in Nepal. The study aimed to assess the prevalence of intestinal parasitosis among patients in a hospital of Nepal. Methods: A retrospective study was done by analyzing the findings of stool examined from April 2006 to March 2008 at Department of Microbiology of the hospital. χ2-test was used for analytical assessment. Results: Out of 2221 fecal samples, 20.7% were positive, the positivity being 23.9% and 15.8%, respectively in first and second year (P<0.05). Overall infection rate was nearly equal in male and female (20.2% vs. 21.2%). The infection rate was highest among patients of >60 years (25.3%) followed by those of <15 years (21.2%) and 15-59 years (20.1%) ( P>0.05). Ascaris lumbricoides (31.8%) and Entamoeba histolytica (38.0%) were the commonest helminth and protozoa, respectively. Other parasites were Hookworm (18.3%), Hymenolepis nana (2.6%), Taenia solium (2.6%), Strongyloides stercoralis (1.3%) and Giardia lamblia (5.5%). Conclusions: Though, the prevalence of intestinal parasitosis among hospital visiting patients is declining, high detection of A. lumbricoides and E. histolytica signifies the need of public awareness regarding latrine use, water source protection from fecal contamination, proper sanitation and hygienic behavior. Keywords: Ascaris lumbricoides, Entamoeba histolytica, intestinal parasites. DOI: 10.3126/joim.v31i3.2974 Journal of Institute of Medicine, December, 2009; 31(3) 13-16